Expropriation of the Jewish Property, and Destruction in Lithuania during the Second World War - Brandišauskas, Valentinas (Genocidas ir rezistencija, 2002)
Institutions of Lithuanian central and local authorities actively took part in ratifying the further fate of the Jewish property. The temporarily government drafted laws of the Soviet government on the denationalization of the nationalized property. These laws were not to be applicable to people of Jewish nationality. The committee for dwellers of Vilnius city and its districts made a list of people who would be the assignees of the Jewish property. The ratification of the fate of the Jewish property was a lot influenced by the district administration. The district officials would often directly participate in evaluating and selling the property. It is evident, that such position of the governmental institutions was publicly indecent and discriminatory. On the other hand, these institutions were not independent; therefore they only reflect the position of individual officers who worked there, but not the position of the Lithuanian state. Representatives of the Lithuanian Catholic Church assessed this severance of the Jewish property only after they had been terminated, i.e. in the summer of 1942, after the majority of Jews had already been exterminated. Considerations regarding the remaining Jewish property can be treated as regret about the tragic fate of Jews. Expropriation of the property is usually reasoned that only in this way the property can be protected from complete destruction. The fate of Jewish property differed, i.e. personal estate was usually given out or sold out to local people; museum pieces, archival valuables were taken to Germany. A lot of Jewish property was left under the supervision of the local administration and was used for its purposes, and also was given to private persons.